Meat selection and preparation [video recording] (Films Media Group, 2013)
Food enthusiasts around the world have long praised meat, in all its varieties, as a pinnacle of culinary delight. But a certain amount of skill is needed to deliver a dish of beef or poultry that is not tough or dried out. In this program, a professional chef gives step-by-step instructions on how to prepare meat before cooking, while also guiding viewers through the identification of different cuts, their packaging and storage, hygiene and safety tips, cleaning and deboning, and even knife selection. Produced in Australia.